Africa and the Formation of the New System of International Relations—Vol. II
XIV, 377 p. 26 illus., 21 illus. in color.
Keywords: In light of the growing number of African summits and a new awareness of international interdependence during the COVID-19 pandemic, this book provides a comprehensive analysis of the current state of Africa’s international relations (IR). Leading IR scholars from Africa and around the world examine international cooperation with African countries in areas such as health care, education, and peacekeeping and explore how Africa’s role in the system of international relations has changed during the COVID-19 pandemic. The book is divided into four parts, the first of which explores analyzes the various actors that constitute African agency in the post-pandemic world, while the second focuses on the summits of the major powers regarding cooperation with Africa. The third part covers public health cooperation and regional initiatives in Africa, including issues such as vaccine diplomacy, while the fourth and final part discusses conflicts & political process despite COVID Pandemics.